In vivo inefficiency of pentoxifylline and interferon-alpha on hepatic fibrosis in biliary-obstructed rats: Assessment by tissue collagen content and prolidase activity - ÜSTAY, ÖZLEM (WILEY, 2003)
Background and Aim: To evaluate the possible antifibrotic effects of two drugs, pentoxifylline (PTX) and interferon (IFN)-alpha as well as their combination, on a bile-duct-ligated rat hepatic fibrosis model. Methods: Bile ducts of 34 female Wistar rats were ligated, and 24 bile ducts were sham operated. Bile-duct-ligated rats were divided into four groups, in which either sterile saline, IFN-alpha (100 000 IU/3 days a week), PTX (50 mg/kg/day) or IFN-alpha + PTX were administered. Sham-operated rats were treated at the same doses. On the 28th day, rats were decapitated to obtain blood for the measurements of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT) and bilirubins. Serum prolidase was assayed at the beginning and at the end of the study by the modified Chinard's colorimetric method. Liver prolidase was assayed after tissue homogenization. Liver collagen content was determined by the dye elution method described by Lopez de Leon. Morphometric-densitometric measurements of hepatic fibrosis were quantified by computerized image analysis. Results: The AST, ALT, ALP, GGT and bilirubins, liver prolidase enzyme activity, collagen content and hepatic collagen surface density were found to be increased in bile-duct-ligated rats on day 28. There was no statistically significant recovery or even a change in collagen turnover rate in rats treated with alternate regimens applied in the study (P > 0.05). Conclusion: Pentoxifylline, IFN-alpha and their combination have no beneficial effect on experimental fibrosis induced by biliary obstruction. (C) 2003 Blackwell Publishing Asia Pty Ltd.
Keywords: antifibrotic; bile duct ligation; combination; hepatic fibrosis; interferon-alpha; pentoxifylline; prolidase; rat; BILE-DUCT OBSTRUCTION; LIVER FIBROSIS; QUANTITATIVE ASSESSMENT; HISTOLOGICAL ACTIVITY; MORPHOMETRIC METHOD; EXPERIMENTAL-MODEL; PLASMA PROLIDASE; SCORING SYSTEM; SERUM MARKERS; C PATIENTS